Aeolian process and climatic changes in loess records from the northeastern Tibetan Plateau: Response to global temperature forcing since 30 ka. (2nd June 2015) - Wang, Xianyan; Yi, Shuangwen; Lu, Huayu; Vandenberghe, Jef; Han, Zhiyong
Abstract: The response of surface processes to global climatic changes since the last glacial is critical to understanding the mechanism of climatic changes on the Tibetan Plateau. In this study, loess from the northeastern Tibetan Plateau (NETP) was closely spaced dated to provide an independent high‐resolution record of dust accumulation processes and millennial‐scale climatic changes. Optically stimulated luminescence ages reveal episodes of rapid dust deposition at approximately 12.3 ka, 16 ka, 21–23 ka, 25–28 ka, and possibly also at 30–33 ka. These episodes are broadly correlated with high‐latitude and marine records cold climatic events, such as the Younger Dryas, Heinrich event 1, and the Last Glacial Maximum. This correlation implies that dust storms in the NETP represent episodic aridification and wind strengthening, which is ascribed to the southward shift of the polar front and the intensification of the Siberian high‐pressure cell that was forced by millennial‐scale cooling in high northern latitudes. Key Points: Loess from northeastern Tibetan Plateau (NETP) dated by high‐resolution OSL ages Dust accumulations were broadly correlated with cold millennial climate events Dust accumulates in the NETP only when the cold events reach to a threshold